2020
DOI: 10.1016/j.psychres.2020.113394
|View full text |Cite
|
Sign up to set email alerts
|

Pilot trial of a transdiagnostic computerized anxiety sensitivity intervention among VA primary care patients

Abstract: Highlights Open pilot trial of computerized anxiety sensitivity intervention among Veterans. High levels of acceptability and usability were found. Qualitative analyses revealed areas of strength/improvement for this intervention. Medium-large effects on depression, anxiety, PTSD, and suicidal ideation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…26 Brief anxiety sensitivity-targeted interventions have been found to produce medium to large effects in reducing anxiety sensitivity and maintain these gains up to 6 months. 27,28 Furthermore, reductions in anxiety sensitivity may be experienced in as little as a single session, regardless of mode of delivery (ie, computerized or in-person), 28,29 Anxiety sensitivity interventions could be delivered to at-risk individuals by a co-located mental health care provider during prenatal visits, by trained prenatal care providers, or via a computer within a prenatal clinic or from the patient's home. 26 Integrating psychiatric services within prenatal offices and other forms of prenatal care (eg, concurrent with midwife or doula visit) can potentially improve access to perinatal mental health treatment and may prevent the development or exacerbation of maternal emotional difficultiesultimately improving outcomes for the woman and infant.…”
Section: Discussionmentioning
confidence: 99%
“…26 Brief anxiety sensitivity-targeted interventions have been found to produce medium to large effects in reducing anxiety sensitivity and maintain these gains up to 6 months. 27,28 Furthermore, reductions in anxiety sensitivity may be experienced in as little as a single session, regardless of mode of delivery (ie, computerized or in-person), 28,29 Anxiety sensitivity interventions could be delivered to at-risk individuals by a co-located mental health care provider during prenatal visits, by trained prenatal care providers, or via a computer within a prenatal clinic or from the patient's home. 26 Integrating psychiatric services within prenatal offices and other forms of prenatal care (eg, concurrent with midwife or doula visit) can potentially improve access to perinatal mental health treatment and may prevent the development or exacerbation of maternal emotional difficultiesultimately improving outcomes for the woman and infant.…”
Section: Discussionmentioning
confidence: 99%
“…Such work has often been successful in reducing anxiety sensitivity and such changes often, but not uniformly, been related to reduced behavioral health problems (Schmidt et al, 2016). Further, anxiety sensitivity reduction has been successfully integrated into therapeutic modules for posttraumatic stress among non-Hispanic White samples (Allan et al, 2015;Norr et al, 2020;Vujanovic et al, 2012). These intervention tactics for posttraumatic stress could be used and further culturally tailored to the non-Hispanic Black population (e.g., framing around trauma and chronic psychosocial stressors, such as racism and racial trauma) with elevated anxiety sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…AS has been implicated in the development and persistence of PTSD (Zoellner et al, 2020) and AUD (Chavarria et al, 2015; Schmidt et al, 2007), and may be a contributing factor in the observed comorbidity of these disorders (Vujanovic et al, 2018). Interventions targeting AS are effective with clients with PTSD (Norr et al, 2020) which indicates a possible mediational role for PTSD and/or AUD. PTSD symptom severity is related to alcohol use via heightened AS in US veterans (Vujanovic et al, 2022), supporting a self‐medicating role for increased drinking.…”
Section: Introductionmentioning
confidence: 99%